O protagonismo feminino em Minas Gerais: Maria Dorotéia Joaquina de Seixas (1767-1853) - Magalhães Jardim, Ana Cristina (Temporalidades, 2019)
The article proposes to discuss the possibility of feminine protagonism in Minas Gerais based on the sources and information gathered about the life of Maria Doroteia Joaquina de Seixas, the woman behind the mith Marília de Dirceu. We try to understand how she and other women sought to live some kind of autonomy within that society.